1
$\begingroup$

I'm having trouble solving this first order linear differential equation. I know the answer (thanks Mathematica!), but I'm having trouble with the steps. The equation is,

$ \begin{align*} y' - \frac{1}{1+x} y = 2 \end{align*} $

I know I have to use an integrating constant, which in this case has to be $\log\left(\frac{1}{1+x}\right) = -\log(1+x)$. So,

$ \begin{align*} -\log(1+x)y &= -2 \int \log(1+x) \\[1em] -\log(1+x)y &=-2\left((1+x)\log(1+x)-x\right) + C \\[1em] \log(1+x)y &= 2\left((1+x)\log(1+x)-x\right) + C \end{align*} $

Not sure how to simplify, as the answer is

$ y = C(1+x) + 2(1+x)\log(1+x) $

Or maybe my approach is wrong.

$\endgroup$

migrated from mathoverflow.net Apr 21 '16 at 18:55

This question came from our site for professional mathematicians.

  • $\begingroup$ An integrating factor is $\mu(x) = (1+x)$ and the "answer" should be $y=(1+x)+C(1+x)^{-1}$... $\endgroup$ – José Hdz. Stgo. Apr 21 '16 at 18:28
1
$\begingroup$

Your current equation reads $$y^{\prime}-\frac1{1+x}y=2$$ First order linear of the form $y^{\prime}+p(x)y=q(x)$ so your integrating factor is $$\mu(x)=e^{\int p(x)dx}=e^{\int\frac{-dx}{1+x}}=e^{-\ln(1+x)}=\frac1{1+x}$$ then rewrite your equation as $$\frac d{dx}\left(\mu(x)y(x)\right)=\frac d{dx}\left(\frac{y}{1+x}\right)=\frac{y^{\prime}}{1+x}-\frac y{(1+x)^2}=\mu(x)q(x)=\frac2{1+x}$$ Now the differential equation has been reduced to quadrature and you can find $$\frac y{1+x}=\int\frac2{1+x}dx=2\ln|1+x|+C$$ So $$y(x)=2(1+x)\ln|1+x|+C(1+x)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.